2022
DOI: 10.52082/jssm.2022.137
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Cooling Reduces Perceived Exertion but Has No Effect on Baseball Hitting or Defense Performance in a Hot Environment

Abstract: Hot environments can impair the complex cognitive functions that are crucial to baseball hitting and defense. This study investigated the effects of intermittent forehead and neck cooling on the hitting and reactive agility of baseball players in hot environments. Ten male collegiate baseball players played 7-inning intrasquad games in a hot environment (31.1°C - 33.4°C), completing one cooling and one control trial in a randomized crossover design. In the cooling trial, the participants placed ice-cold towels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Similarly, Shibasaki et al (2019) found that executive functions decreased after moderate-intensity exercise at heat condition (35 °C, 30%-40% RH) (Shibasaki et al, 2019). Notably, significant improvements were found in Stroop response and more-odd shifting test after using pre-cooling and intermittent mixedcooling strategies, which are inconsistent with the findings of Tessa Maroni (Maroni et al, 2018) and Jyh-How Huang (Huang et al, 2022). Compared with the cooling interventions in the above two studies, the cooling interventions in our study had three main differences.…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, Shibasaki et al (2019) found that executive functions decreased after moderate-intensity exercise at heat condition (35 °C, 30%-40% RH) (Shibasaki et al, 2019). Notably, significant improvements were found in Stroop response and more-odd shifting test after using pre-cooling and intermittent mixedcooling strategies, which are inconsistent with the findings of Tessa Maroni (Maroni et al, 2018) and Jyh-How Huang (Huang et al, 2022). Compared with the cooling interventions in the above two studies, the cooling interventions in our study had three main differences.…”
Section: Discussionmentioning
confidence: 92%
“…Using these defining criteria, nine studies examined level 5 participants (~ 26%) [29,30,86,91,[106][107][108][109][110], 12 studies examined level 4 participants (~ 35%) [82, 87, 88, 92-97, 102, 111, 112], 6 studies examined level 3 participants (~ 18%) [84,89,[113][114][115][116], 9 studies examined level 2 participants (~ 26%) [84, 98-102, 108, 117, 118] and 1 study examined level 1 participants (~ 3%) [84]. One study did not clearly report their participants level of competition [119].…”
Section: Characteristics Of the Participantsmentioning
confidence: 99%
“…Among the 34 included studies, 27 were observational, 5 were experimental (2 parallel group and 3 repeated measures randomised controlled trials), and 2 were quasi-experimental (1 parallel group and 1 repeated measures non-randomised controlled trial). In-competition T c has been reported in tennis [92-97, 100-102, 107, 112, 114, 116], soccer [88,108,109,111,118,119], rugby union [98,99,117], Australian Rules football [29,110,115], rugby sevens [30,91,106], squash [84], judo [87], handball [86], cricket [82], basketball [89] and baseball [113]. Rectal measures of T c were most common and used in 21 studies (~ 62%), whereas gastrointestinal methods were used in 14 studies (~ 41%; one study was forced to use a combination due to technical difficulties with their gastrointestinal devices and thus has been counted in both).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Body cooling strategies may be classified as internal and external cooling strategies. Several studies have investigated the efficacy of external cooling strategies for baseball and cricket players [ 5 , 8 11 ]. External cooling of cricket pitchers was shown to prevent increases in T c , sk , HR, RPE, and TS during bowling simulations in a hot environment [ 5 ].…”
Section: Introductionmentioning
confidence: 99%